2009
DOI: 10.2174/156652409788167050
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Hypoxia as a Modifier of DNA Strand Break and Cross-Link Repair

Abstract: Hypoxia is a common characteristic of many solid tumors and is associated with poor prognosis. Cells with low oxygen levels can have altered sensitivity to radiotherapy and chemotherapy secondary to changes in the incidence of DNA single- and double-strand breaks (DNA-ssb, DNA-dsb), DNA base damage, DNA-DNA cross-links and DNA-protein cross-links. Recent evidence also supports that cells exposed to chronic hypoxia have a decreased capacity of DNA-dsb repair. This review will examine the influence of short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 88 publications
3
25
0
Order By: Relevance
“…4 and Supplementary Figs. S4 and S5) as previously reported (51,52). In that context, we observed that knocking down Nupr1 expression increases cell death, induces DNA damage, and alters the expression of several genes involved in DNA repair, some of them being regulated by hypoxia and by glucose starvation.…”
Section: Discussionsupporting
confidence: 81%
“…4 and Supplementary Figs. S4 and S5) as previously reported (51,52). In that context, we observed that knocking down Nupr1 expression increases cell death, induces DNA damage, and alters the expression of several genes involved in DNA repair, some of them being regulated by hypoxia and by glucose starvation.…”
Section: Discussionsupporting
confidence: 81%
“…18 F-FMISO, 18 F-FAZA, 18 F-EF5, and 60 Cu-ATSM), or single photon emission computed tomography (SPECT;…”
Section: Discussionmentioning
confidence: 99%
“…18). The relative level of oxygen at the time of irradiation determines the efficacy of radiotherapy, by limiting the type and number of lethal DNA lesions (e.g., DNA DSBs).…”
Section: Models Of Hypoxia and Resistance To Radiotherapy And Chemothmentioning
confidence: 99%
“…Koshiji et al demonstrated that Hif-1/HIF-1 (PASD8) inhibits the DNA mismatch repair system (MSH2 and MSH6), which is responsible for genetic instability [8]. Other researchers have also reported that hypoxia down regulates the expression of DNA double-stranded break repair genes [9,10] [11,12]. These data support the concept that defective DNA repair pathways cause genomic instability within the tumor microenvironment.…”
mentioning
confidence: 81%